2019
DOI: 10.2147/ijn.s225594
|View full text |Cite
|
Sign up to set email alerts
|

<p>Manganese Oxide Nanozymes Ameliorate Mechanical Allodynia in a Rat Model of Partial Sciatic Nerve-Transection Induced Neuropathic Pain</p>

Abstract: Background: Reactive oxygen species (ROS) induced oxidative stress is linked to numerous neurological diseases, including neuropathic pain. Natural ROS scavenging enzymes like superoxide dismutase (SOD) and catalase have been found to be efficient in alleviating neuropathic pain. However, their sensitivity towards extreme pH and a short half-life limit their efficacy in vivo. Manganese oxide nanoparticles (MONPs) are recently known to possess ROS scavenging properties. In this study, MONPs were examined for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…Partial sciatic nerve transection surgery was performed by following the procedure reported previously [ 33 , 34 ]. The sciatic nerve from the left leg was carefully pulled until mid-thigh level, then a prolene 7-0 needle was introduced into the nerve just cranially to the branch stretching to the musculus biceps femoris, half of the nerve was transacted in a ventrocranial way up to the ligature.…”
Section: Methodsmentioning
confidence: 99%
“…Partial sciatic nerve transection surgery was performed by following the procedure reported previously [ 33 , 34 ]. The sciatic nerve from the left leg was carefully pulled until mid-thigh level, then a prolene 7-0 needle was introduced into the nerve just cranially to the branch stretching to the musculus biceps femoris, half of the nerve was transacted in a ventrocranial way up to the ligature.…”
Section: Methodsmentioning
confidence: 99%
“…Partial sciatic nerve transection (PSNT) surgery was performed by following our previous protocols [ 31 , 33 , 34 ]. The sciatic nerve from the left leg of rats was gently exposed, and a prolene 7-0 needle was inserted carefully and semi-transected, in an intracranial direction.…”
Section: Methodsmentioning
confidence: 99%
“…Although many underlying mechanisms, related to the onset and development of neuropathic pain, have been suggested, mitochondrial dysfunction may be one of the most important pathophysiological mechanisms of neuropathic pain [3,4]. Our and other previous studies reported that mitochondrial reactive oxygen species (ROS) levels are increased in the neuropathic spinal cord, and that removal of ROS in neuropathic pain can lead to recovery of central sensitization and hyperalgesia to normal levels [5][6][7][8]. In addition to mitochondrial functions and ROS, autophagy has been regarded as one of the most important mechanisms for understanding neuropathic pain.…”
Section: Introductionmentioning
confidence: 84%